2000
DOI: 10.1159/000016095
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lacunar Infarcts

Abstract: Lacunar infarcts represent a stroke subgroup with controversial risk factors. Lacunar syndromes may be divided into two groups: the classic group (pure motor hemiplegia, pure sensory stroke, ataxic hemiparesis, dysarthria-clumsy hand syndrome, sensorimotor stroke) and the miscellaneous group including all other lacunar syndromes. We studied risk factors of 200 consecutive patients with symptomatic lacunar infarcts diagnosed by magnetic resonance imaging. This study tested whether lacunar infarcts represent a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…17,18,22 Despite these findings, the role of hypertension in LI has been questioned, mainly because other causal factors for LI such as embolus of cardiac or carotid origin have been found recently. 3,4,6,7,9,16,23,24 Kappelle and van Gijn 7 revised 14 LI studies and found that 43% to 83% of the patients were hypertensive. In a study of isolated systolic hypertension, Davis et al 25 found that diabetes mellitus and smoking are particularly associated with LI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,22 Despite these findings, the role of hypertension in LI has been questioned, mainly because other causal factors for LI such as embolus of cardiac or carotid origin have been found recently. 3,4,6,7,9,16,23,24 Kappelle and van Gijn 7 revised 14 LI studies and found that 43% to 83% of the patients were hypertensive. In a study of isolated systolic hypertension, Davis et al 25 found that diabetes mellitus and smoking are particularly associated with LI.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] They are traditionally associated with risk factors, natural history, and clinical management that are significantly different from those of other types of brain infarcts. [2][3][4][5][6][7][8] Recently, Boiten et al 9 proposed that 2 distinct LI entities can be distinguished: (1) patients with a single LI and the usual vascular risk factors and (2) patients with multiple LI and a high frequency of hypertension and leukoaraiosis, in which the underlying small-vessel vasculopathy may be different. Although speculative, distinguishing these 2 clinical LI entities may enable more appropriate therapy.…”
mentioning
confidence: 99%
“…However, atypical lacunar syndromes represent a less studied group of LI, and although it is supposed that in such a subgroup the lacunar hypothesis is also met, we have fewer available data. Using multivariate analysis, Besson et al [45]did not find a difference between the frequency of risk factors and vascular concomitants between classic lacunar syndromes and an atypical or miscellaneous lacunar group, concluding that atypical lacunar syndrome is a true variant of lacunar stroke.…”
Section: Recent Advancesmentioning
confidence: 99%
“…Lacunar infarction possesses several noteworthy characteristics including low mortality rate [12, 13, 14]. Although its symptoms are well known as lacunar syndromes, lacunar infarction is more often silent [15, 16].…”
Section: Introductionmentioning
confidence: 99%